The political economy of the Olympics - Misconceptions about sustainability - Hatani, F. (The business of society, 2020)
In the midst of the global coronavirus crisis, the International Olympic Committee (IOC) and the Japanese government finally decided last month to postpone the Tokyo 2020 Olympics until next year. The general public across the world may have different views on the Olympics - positive and negative, or simply indifference. But with regard to the Tokyo Games, there is a fair reason for not just postponing them but reconsidering their relevance and preferably cancelling them altogether. The ongoing Covid-19 pandemic has underscored the long-standing controversies surrounding the Tokyo Olympics, and it is indeed sustainability that is at stake.